Pengaruh Ownership Structure Terhadap Nilai Perusahaan Dengan Firm Size Sebagai Pemoderasi - Hendrik Wijaya; Umi Murtini (Fakultas Bisnis UKDW, 2009)
The objective of this research is to examine the effect of ownership sttacture on firm value. It is also aimed to examine the moderating effict of firm size on the relationship betweenownership structure and firm value. Using all public listed companies on Indonesia Stock Exchange in 2000-2006 as the sample, the result shows that firm size fail to demonstrate itsmoderating effect on the relationship between ownership structure andfirm value.Keywords: Ownership structure, firm value, firm size,